ADAPTATION IN MEDIEVAL ISLAMICATE MEDICAL COMPILATIONS: THE EXAMPLE OF ARROW EXTRACTIONS. - DAS, AILEEN (Journal of Semitic Studies)
Medical compilations from the medieval Islamicate period have been characterized as stagnant on account of their dependence on earlier Graeco-Roman sources. As the authors of these works rarely offer explicit criticism of past theory and practice, their contributions have been defined in terms of their transmission of the classical medical tradition. This paper draws attention to the ways in which medieval medical compilers adapt their source texts to reflect current modes of practice and even personal experiences. In so doing, it examines the reception of Paul of Aegina's (seventh century ce) chapter on the extraction of arrows (Πραγματεία 6.88) in the compilations of al-Rāzī, al-Maǧūsī, al-Zahrāwī, and Ibn Sīnā. I will argue that Paul and his Arabic successors, working in areas of conflict, either modify their respective sources in light of the realities of their practice or contemporary trends in treatment.